Persepsi Mahasiswa Tentang Pengelolaan Pembelajaran Mata Kuliah Program Studi (MKPS) - Nurina Ayuningtya; Nidya Inten Daniswara; Farrah Salsabila; Maula Salamah Saepudin (Risenologi, 2021)
This research aims to determine how students’ perceptions of learning management course study programs in the learning planning system, learning implementation system, and learning evaluation system in the 3-year diploma of cosmetology study program at Jakarta State University. This research uses the descriptive method in the form of a survey and uses frequency distribution data analysis techniques. The target of this research is 130 students of semester 112 and 113 cosmetology students who have taken the courses study program, which is: (1) hair coloring, (2) hairdo styling, (3) hair cutting, (4) hair care, hair pre-styling and hairstyling, (5) modern and modification hairstyling, (6) Indonesian traditional hairstyling and (7) advanced haircutting. The results showed that students' perceptions about the management of learning for study program subjects (MKPS) in the aspect of learning planning were categorized as very good, in the amount of 88%, students' perceptions about the implementation of learning by lecturers were categorized as very good, in the amount of 87% and students' perceptions about learning evaluation were categorized as very good, in the amount of 86%. The result is the overall learning management of study program courses (MKPS) is categorized as very good.